Answer:
you forgot the question
Step-by-step explanation:
Answer:
Step-by-step explanation:
The system of equations is given as
y=x^2-5x+7 - - - - - - - - - - 1
y=2x+1 - - - - - - - - - - - - - - 2
We would equate equation 1 to equation 2, it becomes
x^2-5x+7 = 2x+1
x^2-5x+7- 2x - 1 = 0
x^2-5x+7- 2x - 1 = 0
x^2 - 5x - 2x + 7 - 1 = 0
x^2 - 7x + 6 = 0
We would use the factorization method of solving quadratic equations.
x^2 - 6x - x + 6 = 0
x(x - 6) - 1(x - 6)
(x - 6)(x - 1) = 0
x - 6 = 0 or x - 1 = 0
x = 6 or x = 1
Substituting both values of x into equation 2, it becomes
For x = 6,
y=2×6 + 1 = 12 + 1 = 13
y = 13
For x = 1,
y=2 × 1 +1 = 2 + 1 = 3
y = 3
Answer:
43
Step-by-step explanation:
you find the answer then fart in a jar and throw it at ur grandma
Answer:
1. y = -3^ x Translated up by 1 unit 2.
2.y = 3^ -x Reflected over the y-axis 3.
3.y = 3 ^x - 2 Translated right by 2 units 4.
4. y = 3 ^x + 1 Translated down by 2 units 5.
5. y = 3^ x + 1 Translated left by 1 unit 6.
6. y = 3 ^x - 2 Reflected over the x-axis
Step-by-step explanation:
Answer: 1 hour is equal to 46 miles 2 hours is 92 miles and 20 hours is 920 miles
Step-by-step explanation:
92/2 = 46 miles
46 x 2 = 92 miles
46 x 20 = 920